Mapping research trends in ethnomathematics within mathematics education: A bibliometric study - Fauzan, Muh. Ikhwan; Rosnawati, Raden; Salsabila, Azkiya; Sutrimo, Moh. Slamet; Ulwiyah, Sa'adatul; Iqbal, Muhammad (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2025)
Ethnomathematics integrates cultural values and local knowledge into mathematics education, fostering contextual and inclusive learning. However, a comprehensive mapping of its scholarly development is still lacking, prompting the need for a bibliometric analysis to explore its contributions and future directions. This study analyses the development of ethnomathematics studies in education using a bibliometric approach based on data from Scopus during the period 2009–2024. This study aims to identify publication trends, authors, publishers, and influential journals, including patterns of relationships between keywords, collaboration between authors, and geographical distribution of publications. The identification results are used to see an overview of the contribution and implications of ethnomathematics in mathematics education. A total of 254 selected articles were analysed using the PRISMA model, R software with the biblioshiny package, and the VOSviewer application. The analysis results show growth with Indonesia as the most significant contributor. The dominant keyword is Ethnomathematics, which focuses on cultural integration in mathematics teaching. This study emphasises the importance of the ethnomathematics approach in improving students' understanding and learning outcomes, enriching cultural insights, and strengthening international collaboration in educational research. The results also show that ethnomathematics has received growing attention in mathematics education research, as reflected in the increasing number of publications and thematic focus in recent years. Recommendations for further research include a deeper exploration of the values of ethnomathematics and its effectiveness in learning.